A stochastic model that explains axonal organelle pileups induced by a reduction of molecular motors. Issue 148 (30th November 2018) - Lai, Xiulan; Brown, Anthony; Xue, Chuan
Abstract : Nerve cells are critically dependent on the transport of intracellular cargoes, which are moved by motor proteins along microtubule tracks. Impairments in this movement are thought to explain the focal accumulations of axonal cargoes and axonal swellings observed in many neurodegenerative diseases. In some cases, these diseases are caused by mutations that impair motor protein function, and genetic depletion of functional molecular motors has been shown to lead to cargo accumulations in axons. The evolution of these accumulations has been compared to the formation of traffic jams on a highway, but this idea remains largely untested. In this paper, we investigated the underlying mechanism of local axonal cargo accumulation induced by a global reduction of functional molecular motors in axons. We hypothesized that (i) a reduction in motor number leads to a reduction in the number of active motors on each cargo which in turn leads to less persistent movement, more frequent stops and thus shorter runs; (ii) as cargoes stop more frequently, they impede the passage of other cargoes, leading to local 'traffic jams'; and (iii) collisions between moving and stopping cargoes can push stopping cargoes further away from their microtubule tracks, preventing them from reattaching and leading to the evolution of local cargo accumulations. We used a lattice-based stochastic model to test whether this mechanism can lead to the cargo accumulation patterns observed in experiments. Simulation results of the model support the hypothesis and identify key questions that must be tested experimentally.